Magnetospheric compressions, magnetopause shadowing and the last-closed-drift-shell - Desai,R; Eastwood,J; Eggington,J; Chittenden,J; Horne,R (2022)
Fluxes in the outer radiation belt can vary by orders of magnitude in response to solar wind driving conditions. Magnetopause shadowing, where electron and proton drift paths intersect the magnetopause boundary, is a fundamental loss process which operates on sub-day timescales and can result in rapid loss across the outer radiation belt. Accurate characterisation of this is therefore required to fully account for outer radiation belt dynamics and to avoid unrealistic fluxes impacting long-term forecasts. In this paper we utilise particle simulations of the radiation belts integrated within evolving global MHD simulations, to provide high-resolution high-fidelity simulations of the phenomenon of magnetopause shadowing. We model a variety of magnetopause compression scenarios corresponding to extreme cases of interplanetary shock impacts, and gradual increases in solar wind dynamic pressure. We thus constrain how time-dependent topological variation of the magnetospheric fields results in a complex interplay of open and closed particle drift paths, and examine the role of the electric field in modulating escaping particles trajectories as well as corresponding prompt injections into the inner magnetosphere.